Technopreneurship Development: Entrepreneurship Ecosystem Analysis in Tasikmalaya - Yusuf, Ismail Yusuf; Koeswandi, Tika Annisa; Fauziyah, Azizah Fauziyah (A Social Science and Entrepreneurship Journal, 2023)
Entrepreneurship is currently an interesting topic in academic discussions because it is considered a solution for a country's economic development. However, the entrepreneurship ratio in Indonesia is currently still very low, reaching 3.47% of the total population of Indonesia. This figure is still lower than neighboring countries such as Singapore 8.76%, Thailand 4.26% and Malaysia with 4.74%. One area of entrepreneurship that is expected to encourage the business ecosystem in Indonesia is the field of technology entrepreneurship. Technopreneurship itself refers to entrepreneurial practices that focus on the development and application of innovative technology. It involves the process of creating, developing, and marketing technology-based products or services. Currently, the concrete step that is most likely to be taken is entrepreneurship. For this reason, a business development model is needed that is adapted to the needs of the technology entrepreneurship ecosystem in Tasikmalaya.